2017
DOI: 10.1016/j.preteyeres.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Roles of exosomes in the normal and diseased eye

Abstract: Exosomes are nanometer-sized vesicles that are released by cells in a controlled fashion and mediate a plethora of extra- and intercellular activities. Some key functions of exosomes include cell-cell communication, immune modulation, extracellular matrix turnover, stem cell division/differentiation, neovascularization and cellular waste removal. While much is known about their role in cancer, exosome function in the many specialized tissues of the eye is just beginning to undergo rigorous study. Here we revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 271 publications
(338 reference statements)
3
127
0
1
Order By: Relevance
“…1E,F). Finally, as the ExoQuick-TC method used here for vesicle isolation might also isolate lipoprotein particles [39] and RPE cells release a range of modified lipoprotein particles, [40] ELISA measurements were performed to determine the ratio between syntenin-1 (exosome marker) [41] and ApoB (modified lipoprotein particle and secreted by ARPE-19 cells) [42]. All samples contained syntenin-1, whereas no ApoB was detected (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1E,F). Finally, as the ExoQuick-TC method used here for vesicle isolation might also isolate lipoprotein particles [39] and RPE cells release a range of modified lipoprotein particles, [40] ELISA measurements were performed to determine the ratio between syntenin-1 (exosome marker) [41] and ApoB (modified lipoprotein particle and secreted by ARPE-19 cells) [42]. All samples contained syntenin-1, whereas no ApoB was detected (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In early AMD, the RPE is thought to contribute to the formation of drusen (extracellular material that builds up between the RPE and Bruch’s membrane). Wang et al, had proposed that exosomes released from aged RPE might contribute to the formation of drusen [50], and polarized release of exosomes from RPE cells has been described in cultured RPE cells [39, 82, 83]. In addition to damaging effects, exosomes released from the RPE are also thought to contribute to neuroptrotection in the retina [84].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are naturally found in common body fluids, including blood, saliva, urine, and breast milk. Accumulated data have implicated that exosomes are involved in intercellular communications through transporting protein, nucleic acid, and other constituents with biological activities . Given the crucial role of exosomes in the regulation of biological processes, relevant research becomes hot, particularly in cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously established that EVs, particularly exosomes, play a central role in the proliferation, migration and tube formation of endothelial cells in different biological systems—in both physiological and pathological scenarios—by either increasing or reducing angiogenesis. Furthermore, RPE cells seem to release specific exosomes through the basolateral membrane towards the choroidal ECs . These exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RPE cells seem to release specific exosomes through the basolateral membrane towards the choroidal ECs. 48,49 These exosomes. An earlier study showed that stressed RPE cells released numerous exosomes expressing VEGFR2 which, when exposed to endothelial cells, hasten their growth.…”
Section: Discussionmentioning
confidence: 99%